Fundamentals of scientific thinking in Islamic tradition - Shogar, Ibrahim Adam Ahmed (IIUM Press, International Islamic University Malaysia, 2018)
This article investigates fundamentals of scientific thinking in Islamic tradition to elucidate its epistemological and cultural elements. The phrase ‘Scientific Thinking’ is generally used for the intellectual activity which encompasses both the content of knowledge and set of reasoning processes that permeate the field of acquiring knowledge. Formation of systematic mind, systemization of inquiry, and construction of an objective research method are the major characteristics of scientific thinking. The investigation on source, cause, and aspects of systemization of inquiry is, therefore, contributes immensely in development of scientific enterprise. The major approaches in the history of science that contributed in systemization of inquiry are such as the rational approach that espoused by the ancient Greek philosophy, formation of scientific mind that introduced by the Qur’anic revelation to investigate the natural phenomena, and the experimental method of modern science that based on systematic observation. This article aims to investigate the case of Qur’anic approach to investigate nature and its contribution in developing matrix of scientific thinking in Islamic tradition. The Qur’anic exposure of human thought to the natural phenomena based on systematic observation had contributed and played a major role in development of science in early history of Islamic civilization, preservation of scientific legacy of ancient civilizations, and subsequently have caused the emergence of modern science. The major characteristics and the peculiar features of scientific thinking in Islamic tradition will be investigated. The epistemological and cultural aspects of scientific thinking in Islamic tradition will be investidated as well.